Reductions in COQ2 Expression Relate to Reduced ATP Levels in Multiple System Atrophy Brain - Hsiao, Jen-Hsiang T.; Purushothuman, Sivaraman; Jensen, Poul H.; Halliday, Glenda M.; Kim, Woojin Scott (Frontiers in Neuroscience, 2019)
Multiple system atrophy (MSA) is a progressive neurodegenerative disease clinically characterized by parkinsonism and cerebellar ataxia, and pathologically by oligodendrocyte alpha-synuclein inclusions. Genetic variants of COQ2 are associated with an increased risk for MSA in certain populations. Also, deficits in the level of coenzyme Q10 and its biosynthetic enzymes are associated with MSA. Here, we measured ATP levels and expression of biosynthetic enzymes for coenzyme Q10, including COQ2, in multiple regions of MSA and control brains. We found a reduction in ATP levels in disease-affected regions of MSA brain that associated with reduced expression of COQ2 and COQ7, supporting the concept that abnormalities in the biosynthesis of coenzyme Q10 play an important role in the pathogenesis of MSA.